Editorial (American Journal of Islam and Society, 2009)
Even though interdisciplinary approaches to the study of humanity are increasinglya preferred method of study, it is still easy for scholars to isolate themselves withintheir field and lose touch with developments in the rest of the academy. Therefore,interdisciplinary journals such as AJISS are vital tools for helping them to keepabreast of the latest developments in areas outside their discipline but still in theirrealm of interest – in the case ofAJISS, the study of Islam andMuslims, both historicallyand contemporaneously.This issue of AJISS features outstanding essays from several academic disciplines:history, Islamic studies, management, and philosophy.We open withMuhammadAziz’sstudy of the rise of Sufism inYemen, “AShort Survey of Yemeni Sufismfrom Its Inception to the Thirteenth Century.” Aziz argues that a tradition of asceticismby Yemeni Muslims, including such prominent Companions as Abu Hurayrah,developed into themore institutionalized Sufismthat appeared and was spread by theAyyubid dynasty during the eleventh to twelfth centuries. He maintains that tracingthe history of Yemeni asceticism and Sufism is important because of the political, aswell as religious, role that its leading practitioners had on Yemeni life ...